Schwannoma Presenting As Pituitary Macroadenoma: Case Report - Poudel, Hari; Bhandari, Rajeev; Khambu, Bikesh Kumar; Shrestha, Rajendra; Jha, Rajeev; Bista, Prakash (Nepal Journal of Neuroscience, 2019)
Schwannoma is common intracranial tumor. They are benign tumor arising from Cranial nerves or peripheral nerves. Majority of these tumors occur at Cerebellopontine angle. 54-year right handed lady presented with history of progressive loss of vision on both eyes for last five years. It started on her left eye initially pronounced on lateral field which gradually progressed to involve right eye. MRI of brain showed a well-defined mass of size 39*35*29mm in sellar region extending to suprasellar region with T1 is intensity and T2 hyperintensity. Endonasal trans-sphenoidal resection of lesion was done guided by navigation. Surprisingly histopathology turned out to be Schwannoma.